Peningkatan Profesionalitas Pendidik dan Tenaga Kependidikan melalui Workshop Charge and Recharge di Pesantren Tahfidhul Qur'an Al-Umm Smart Center - Syafri, Muhammad; Ningrum, Dhea Agusty (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to enhance the professionalism of teachers and staff at the Pesantren Tahfidhul Qur'an Al-Umm Smart Center through the "Charge & Recharge" workshop. Action Research method is employed with planning, action, observation, and reflection stages. The workshop involves teachers and staff in planning, implementation, and evaluation. The results indicate improvements in teaching competence, classroom management, and managerial skills. Evaluation employs questionnaires, interviews, observations, and participant-facilitator reflections. The outcomes of evaluation and reflection are analyzed to identify strengths and weaknesses of the workshop, providing feedback for future competence development activities for teachers and staff. The workshop proves effective in enhancing the professionalism and performance of teachers and staff, with identified strengths such as interactive methods and weaknesses such as the workshop's short duration. In conclusion, the "Charge & Recharge" workshop offers relevant and effective training, emphasizing sustainable self-development for participants. Thus, this endeavor can bolster the quality of education and management at the pesantren.